2016
DOI: 10.1161/circresaha.115.306647
|View full text |Cite
|
Sign up to set email alerts
|

Role of Brown Fat in Lipoprotein Metabolism and Atherosclerosis

Abstract: Atherosclerosis, for which hyperlipidemia is a major risk factor, is the leading cause of morbidity and mortality in Western society, and new therapeutic strategies are highly warranted. Brown adipose tissue (BAT) is metabolically active in human adults. Although positron emission tomography-computed tomography using a glucose tracer is the golden standard to visualize and quantify the volume and activity of BAT, it has become clear that activated BAT combusts fatty acids rather than glucose. Here, we review t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(149 citation statements)
references
References 108 publications
5
141
1
2
Order By: Relevance
“…8 Physiologically, BAT is activated by cold exposure. 9 10 Indeed, prolonged cold acclimatization recruits BAT activity 10 and is able to induce modest weight loss.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…8 Physiologically, BAT is activated by cold exposure. 9 10 Indeed, prolonged cold acclimatization recruits BAT activity 10 and is able to induce modest weight loss.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…Findings from mouse models demonstrate that cold-activated BAT can effectively clear plasma triglycerides [4850] and may even mitigate hypercholesterinemia and suppress the formation of atherosclerotic plaque [51, 52, 49]. One study demonstrated a retardation of atherosclerotic plaque growth with only 8 weeks of cold exposure [53]; however, this may have been the result of rapid exposure instead of gradual acclimation.…”
Section: Contributions Of Bat To Energy Metabolism Glucose Metabolismentioning
confidence: 99%
“…In response to cold, norepinephrine is released from the sympathetic nervous system and binds to β adrenergic receptors on brown and beige adipocytes; this leads to the activation of the adenylyl cyclase/cAMP/protein kinase A (PKA) signaling cascade required for the hydrolysis of intracellular TG. PKA phosphorylates and activates cAMP response element-binding protein (CREB) resulting in enhanced transcription of UCP1 and peroxisome proliferator-activated receptor-γ [93]. Kuji et al [94] observed that patients with high plasma catecholamines, due to pheochromocytoma, during PET/CT exams have increased FDG uptake in the cervical, paravertebral, mediastinal, and perirenal regions, suggesting activation of BAT.…”
Section: Browning Of Wat As a Possible Aid To Fight Metabolic Diseasesmentioning
confidence: 99%